Reactive application development - DeVore, Duncan K.; Walsh, Sean; Hanafee, Brian (Manning Publications, 2018)
Mission-critical applications have to respond instantly to changes in load, recover gracefully from failure, and satisfy exacting requirements for performance, cost, and reliability. That's no small task! Reactive designs make it easier to meet these demands through modular, message-driven architecture, innovative tooling, and cloud-based infrastructure. Reactive Application Development teaches you how to build reliable enterprise applications using reactive design patterns. This hands-on guide begins by exposing you to the reactive mental model, along with a survey of core technologies like the Akka actors framework. Then, you'll build a proof-of-concept system in Scala, and learn to use patterns like CQRS and Event Sourcing. You'll master the principles of reactive design as you implement elasticity and resilience, integrate with traditional architectures, and learn powerful testing techniques.